Quick Parking Enterprise / Jabrullah Kadir...[et.al] - Kadir, Jabrullah; Ab Majid, Mohd Faiq; Abd Wahed, Mohd Akhbar Muqriz; Samion, Nur Syafiqah; Osman, Siti Fatihah; Ahmad, Siti Norain (Faculty of Plantation and Agrotechnology, 2014)
Quick Parking Enterprise is a company related to the technology-based parking system. Our product is branded as e-Parking. The market focus is for any shopping complexes, airport and office buildings who are interested to implement our technology at their parking area. Our business is commenced on 2014 and our vision is to make our company a well-known, established and satisfied by our customer in order to expand our capacity of our systems and to attract other companies to deal with us with a better price. This will be realized by the full cooperation and efforts among the partners to promote this company. Based on the objectives above, we are venturing into technology-based industry. e-Parking has the potential of being a relevant and profitable business as it is an innovation technology that could contribute to some solutions to parking issues at the shopping complexes, airport and office buildings and facilitate consumers as well. We will expect that our business will become more developed in the near future because currently the need of solution for parking problem has become people's awareness. We confident that the technology we brought would help solving the parking issues. Indirectly, this opportunity will give us more advantages to make our product more profitable and stable in the long run.